Pimozide reduces toxic forms of tau in TauC3 mice via 5′ adenosine monophosphate‐activated protein kinase‐mediated autophagy. Issue 5 (11th July 2017) - Kim, Young Doo; Jeong, Eun Il; Nah, Jihoon; Yoo, Seung‐Min; Lee, Won Jae; Kim, Youbin; Moon, Seowon; Hong, Se‐Hoon; Jung, Yong‐Keun
Abstract: In neurodegenerative diseases like Alzheimer's disease (AD), tau is hyperphosphorylated and forms aggregates and neurofibrillary tangles in affected neurons. Autophagy is critical to clear the aggregates of disease‐associated proteins and is often altered in patients and animal models of AD. Because mechanistic target of rapamycin (mTOR) negatively regulates autophagy and is hyperactive in the brains of patients with AD, mTOR is an attractive therapeutic target for AD. However, pharmacological strategies to increase autophagy by targeting mTOR inhibition cause various side effects. Therefore, autophagy activation mediated by non‐mTOR pathways is a new option for autophagy‐based AD therapy. Here, we report that pimozide activates autophagy to rescue tau pathology in an AD model. Pimozide increased autophagic flux through the activation of the AMPK‐Unc‐51 like autophagy activating kinase 1 (ULK1) axis, but not of mTOR, in neuronal cells, and this function was independent of dopamine D2 receptor inhibition. Pimozide reduced levels of abnormally phosphorylated tau aggregates in neuronal cells. Further, daily intraperitoneal ( i.p.) treatment of pimozide led to a recovery from memory deficits of TauC3 mice expressing a caspase‐cleaved form of tau. In the brains of these mice, we found increased phosphorylation of AMPK1 and ULK1, and reduced levels of the soluble oligomers and NP40‐insoluble aggregates of abnormally phosphorylated tau. Together, these results suggest that pimozide rescues memory impairments in TauC3 mice and reduces tau aggregates by increasing autophagic flux through the mTOR‐independent AMPK‐ULK1 axis. Abstract : Because autophagy‐based AD therapy with mTOR as a target has side effects, other alternatives are needed. We found that pimozide increased autophagic flux through the activation of the AMPK‐ULK1 axis. Through this process, pimozide reduced levels of abnormally phosphorylated tau aggregates and rescued memory impairments in AD mouse model, providing insight into a therapeutics for tau‐mediated neuropathology in AD.